Transungual Drug Delivery System for the Topical Treatment of Onychomycosis: A Review - Giri, Yashwant; Behera, Amulyaratna; Mohanty, Biswaranjan; Pattnaik, Gurudutta; Habibullah, S.K. (Drug Delivery Letters, 2022)
Onychomycosis is an infection caused by a fungus that causes discoloration and thickening of the nail layer, and it is the most common nail infection in the world. Trichophyton rubrum and Trichophyton mentagrophytes var. interdigital is the most common anthropophilic dermatophytes that trigger it. Onychomycosis is caused by yeasts such as Candida albicans and Candida parapsilosis, as well as moulds such as Aspergillus spp. Treatment is determined by the type of nail invasion, the fungus genus, and the number of nails affected. Approaches towards conventional methods showed certain drawbacks, which emphasizes the need for alternate approaches to produce better therapeutic efficacy of a product. The present review focused on reporting an updated classification of Onchyomycosis, causative organisms, factors influencing drug permeation, novel treatment strategies for Onychomycosis, and drug permeation enhancement methods.
Keywords: transungual